2012
DOI: 10.1103/physrevlett.108.168701
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Coagulation of Nodes in an Evolving Complex Network

Abstract: We propose a new type of stochastic network evolution model based on annihilation, creation, and coagulation of nodes, together with the preferential attachment rule. The system reaches a unique quasistatistically steady state in which the distribution of links follows a power law, lifetime of nodes follows an exponential distribution, and the mean number of links grows exponentially with time. The master equation of the model is solved analytically by applying Smoluchowski's coagulation equation for aerosols.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
68
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 54 publications
(79 citation statements)
references
References 24 publications
(34 reference statements)
11
68
0
Order By: Relevance
“…17.1, the parameter is estimated as 0:078. This value is close to 0:053 reported in [18], and is also close to around 0:05 reported in [17]. T/ and N.T/ is closely related to the constant decay rate of firm activities that does not depend on the age of firms.…”
Section: Age Distribution Of Firmssupporting
confidence: 53%
See 1 more Smart Citation
“…17.1, the parameter is estimated as 0:078. This value is close to 0:053 reported in [18], and is also close to around 0:05 reported in [17]. T/ and N.T/ is closely related to the constant decay rate of firm activities that does not depend on the age of firms.…”
Section: Age Distribution Of Firmssupporting
confidence: 53%
“…Several studies reported that the age distribution of firms obeys an exponential function [17,18]. Since some firms still exist that were founded over 100 years ago, the age distribution of firms, which is observed at a point in time, must be related to long-term statistical laws.…”
Section: Introductionmentioning
confidence: 99%
“…Based on this discussion, Miura, Takayasu and Takayasu [8] proposed a new general network evolution model (MTT model).…”
Section: Empirical Data Analysismentioning
confidence: 99%
“…In addition, both distributions of in degrees and out degrees are roughly the same. Miura et al [8] used the data that cannot be distinguished between established firms and merged firms. Therefore, they decided to set each preferential exponent b D c D 1 for their simulation.…”
Section: Exponent Of Preferential Attachmentmentioning
confidence: 99%
“…Observed in the short-term, non-Gibrat's law and Gibrat's law are related to early power-law and subsequent exponential growth observed in the long-term. The other is firm age distribution (For instance, see [39]- [42]). …”
Section: Introductionmentioning
confidence: 99%